Studi Kasus Tindak Pidana Penganiyaan Dari Pasal 351 Kitab Undang-Undang Hukum Pidana: Studi Kasus Perkara Keputusan yang Berkeadilan 689/Pid.B/2018/PN Jkt. Sel - Budi Santoso; D Andry Effendy (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2025)
This research aims to uncover evidence of the criminal act of persecution (assault) and to conduct a juridical analysis of the judge's decision in a criminal case, as outlined in Decision Number: 689/Pid.B/2018/PN Jkt. Sel. Criminal law is one of the legal instruments that governs societal life, particularly in determining which acts are categorized as criminal offenses and the appropriate sanctions for perpetrators. The primary goal of law is to uphold justice in order to establish public order and peace. Based on this understanding, actions that violate the law and deviate from established norms are classified as criminal acts of persecution, as regulated under Article 351 of the Indonesian Penal Code (KUHP). In this study, the act of persecution discussed is not an ordinary one, but rather a form committed by an offender who abused their official position, which constitutes an aggravating circumstance in sentencing. The court decision in this case is closely related to the application of Article 351 of the Penal Code. This study employs a normative juridical approach, utilizing primary, secondary, and tertiary legal sources. Data collection was carried out through document analysis or library research. The method of data analysis used is legal interpretation, particularly through systematic interpretation. The results of the study conclude that the evidence of the criminal act of persecution in case Number: 689/Pid.B/2018/PN Jkt. Sel. is in accordance with the provisions stipulated in Article 351 of the Penal Code. This conclusion is based on legal considerations drawn from facts revealed during the trial, which served as the basis for the judge’s ruling.